DESIGNING A GREEN MOSQUE IN DELI SERDANG WITH THE APPLICATION OF ISLAMIC ARCHITECTURAL STYLE - Fatimah, Nur; Sembiring , Sri Gunana (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
Indonesian society, with its strong socialist and religious characteristics, shows dynamic growth in economic, socio-cultural, and population aspects. This growth demands the availability of adequate facilities and infrastructure, including representative worship facilities for the majority religious group, namely Islam. In Deli Serdang Regency, North Sumatra, an area with significant ethnic and cultural diversity and a majority Muslim population (68.24%), the need for a mosque as a spiritual and social center is increasing. In addition to serving as a place of worship, the mosque may also develop into a hub for community outreach and Islamic propagation. The design of this mosque aims to create a building of worship that not only fulfills its main function, but also integrates basic Islamic values, accommodates essential supporting facilities and utilizes the potential of the site optimally to create a functional space without wasted areas. The design approach carried is the concept of a "Green Mosque" which emphasizes the principles of sustainability and environmental friendliness, combined with an Islamic architectural style that is relevant to the local context of Deli Serdang. Through an adaptive Islamic architectural approach and green design principles, this design is expected to produce a mosque that is not only aesthetically beautiful and spatially functional, but also makes a positive contribution to the environment and strengthens Islamic identity in the context of the heterogeneous Deli Serdang community. This mosque is expected to be a harmonious reflection of Islamic spiritual values, the social needs of the community, and environmental sustainability.